Persebaran Minimarket dalam Analisis Spasial dan Faktor-faktor yang Mempengaruhinya di Kecamatan Padang Barat - Imaarah, Ainiyah; Yulfa, Arie (Lembaga Yasin AlSys, 2024)
The modern retail industry is experiencing rapid development. One of the currently existing and growing segments is the minimarket. This study was conducted in the Padang Barat District with the aims of: (1) Identifying the factors influencing the distribution pattern of minimarkets in Padang Barat District. (2) Determining the distribution pattern of minimarkets in Padang Barat District. This research is descriptive with a quantitative approach. The method used is the Average Nearest Neighbour or nearest neighbor analysis to determine the distribution pattern of minimarkets. Meanwhile, the factors influencing the location of minimarkets refer to SNI Regulation No. 03 of 2004 and Padang Mayor Regulation No. 53 of 2021, considering demographic aspects, service coverage, and road networks. The results show that there are 21 minimarkets spread across the Padang Barat District. Demographic factors, service coverage, and road networks influence the distribution of minimarket locations. Regarding demographics, calculations suggest the possibility of adding 153 minimarkets, service coverage calculations suggest the possibility of adding 4 minimarkets, and 15 minimarkets are found to be suitable based on the road network. The distribution pattern of minimarkets in Padang Barat District is random, with a T value of 0.949561, a z-score of -0.442191, and a significance value of p 0.658351.